Green application of ultrasonic waves for extraction of yellow colorant from haar singhar and its colouring behaviour in cotton dyeing - ÖZOMAY, MERAL (My University, 2023)
Natural dyes have grown in popularity due to their eco-friendliness. They can be used as a substitute for synthetic dyes to minimize environmental pollution. This research investigates the natural colouring behaviour of haar singhar flower (HSF) extract in cotton dyeing. Colorant was extracted under various conditions utilizing various extraction mediums such as aqueous, basic, and acidic. On cotton, it was discovered that applying 55 mL of aqueous extract containing 1.5 g/100 mL sodium chloride for 40 minutes at 70 °C yielded the best colour output. A new hue with good colour fastness was developed utilizing chemical and bio-mordants. The existence of nyctanthin as a colouring agent in haar singhar flowers was discovered through FTIR analysis of the extract. The CIE Lab system revealed that using 2 g/100 mL of pistachio shell as a bio-mordant resulted in good quality reddish yellow hues. It was discovered that ultrasonic radiations have a high potential for isolating colourants and dyeing cotton fabric under decreased conditions of temperature, time and volume. The application of biomordants has made the procedure greener, more efficient, and safer.
Keywords: Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, ÇEVRE; MALZEME BİLİMİ, BİYOMATERYAL; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, ENVIRONMENTAL; MATERIALS SCIENCE, BIOMATERIALS; ENGINEERING, MANUFACTURING; Kimya (çeşitli); Fizik Bilimleri; Malzeme Bilimi (çeşitli); Atık Yönetimi ve Bertarafı; Endüstri ve İmalat Mühendisliği; Chemistry (miscellaneous); Physical Sciences; Materials Science (miscellaneous); Waste Management and Disposal; Industrial and Manufacturing Engineering; bio mordants; chemical mordants; cotton; haar singhar; nyctanthin; ultrasound